Flyscan opportunities in medicine: the case of quantum rattle based on gold quantum dots. (7th August 2017) - Esteve, Emmanuel; Reguer, Solenn; Boissiere, Cédric; Chanéac, Corinne; Lugo, Gustavo; Jouanneau, Chantal; Mocuta, Cristian; Thiaudière, Dominique; Leclercq, Nicolas; Leyh, Bernard; Greisch, Jean-François; Berthault, Julien; et al.
Abstract : A complete set of data is presented, acquired using the Flyscan method after injection of gold‐cluster‐enriched mesoporous silica nanospheres, used as potential theranostic vectors, into rats. Abstract : The new rapid scan method, Flyscan mode, implemented on the DiffAbs beamline at Synchrotron SOLEIL, allows fast micro‐X‐ray fluorescence data acquisition. It paves the way for applications in the biomedical field where a large amount of data is needed to generate meaningful information for the clinician. This study presents a complete set of data acquired after injection of gold‐cluster‐enriched mesoporous silica nanospheres, used as potential theranostic vectors, into rats. While classical X‐ray fluorescence investigations (using step‐by‐step acquisitions) are based on a limited number of samples (approximately one per day at the DiffAbs beamline), the Flyscan mode has enabled gathering information on the interaction of nanometer‐scale vectors in different organs such as liver, spleen and kidney at the micrometer scale, for five rats, in only a single five‐day synchrotron shift. Moreover, numerous X‐ray absorption near‐edge structure spectra, which are beam‐time‐consuming taking into account the low concentration of these theranostic vectors, were collected.